Iron-based nanocrystalline alloy with high saturation magnetic polarization strength and preparation method of iron-based nanocrystalline alloy

By optimizing the ratio and heat treatment process of iron-based nanocrystalline alloys, the problem that iron-based nanocrystalline alloys in the prior art is difficult to have high saturation magnetic polarization strength and low coercive force, and efficient soft magnetic performance improvement and suitableness are achieved. Process performance of industrial production.

CN119433387APending Publication Date: 2025-02-14TSINGHUA UNIVERSITY
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310961003.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-01
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The existing iron-based nanocrystalline alloys are difficult to have high saturation magnetic polarization strength and low coercive force, poor amorphous formation ability, soft magnetic properties need to be further improved, and poor annealing process performance is not suitable for industrial production.

Method used

By optimizing the ratio of Fe, B, C, Si, P, Cu, and M, it is ensured that the percentage of carbon atoms is not less than the percentage of silicon and phosphorus. M is at least one of V, In, Bi and Sn, and adopts The amorphous alloy strip is prepared by a single-roll rotary quenching method and the difference between the first crystallization temperature and the second crystallization temperature of the amorphous alloy strip is greater than 100K.

Benefits of technology

It achieves a high saturation magnetic polarization strength of no less than 1.8T and low coercivity, which is suitable for industrial production, and improves the soft magnetic properties and process performance of amorphous alloys.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119433387A_ABST
    Figure CN119433387A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of preparation of soft magnetic metal materials, and particularly relates to an iron-based nanocrystalline alloy with high saturation magnetic polarization strength and a preparation method of the iron-based nanocrystalline alloy. The iron-based nanocrystalline alloy with high saturation magnetic polarization strength has a general formula of FeaBbCcSidPeCufMg, wherein a, b, c, d, e, f and g respectively represent the atomic percentages of Fe, B, C, Si, P, Cu and M; the atomic percentage of carbon is not lower than the atomic percentage of silicon and the atomic percentage of carbon is not lower than the atomic percentage of phosphorus; or the sum of the atomic percentages of carbon and phosphorus is not less than the atomic percentage of silicon. The iron-based nanocrystalline alloy with high saturation magnetic polarization strength has the advantages of high iron content, high saturation magnetic polarization strength and low coercive force, does not contain other metal elements (such as noble metals), easily oxidized elements, high-melting-point elements and the like except necessary copper and trace vanadium, indium, bismuth and tin, is low in raw material cost and low in requirements on industrial production equipment, and is beneficial to industrial production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of soft magnetic metal material preparation, and in particular relates to an iron-based nanocrystalline alloy with high saturation magnetic polarization intensity and a preparation method thereof. Background Art

[0002] Due to the rapid development of power electronics, communications, motors, intelligent manufacturing and other fields and the demand for high-performance devices, the improvement of the magnetic properties of soft magnetic materials has received extensive attention from the scientific and industrial communities in recent years. Among the new generation of high-performance soft magnetic materials, iron-based nanocrystalline alloys exhibit low coercivity (H c ), high magnetic permeability and low iron loss, which have given rise to a boom in the research and development of iron-based nanocrystalline alloys.

[0003] Iron-based nanocrystalline alloy is a multiphase alloy composed of a high volume fraction of α-Fe nanocrystals and a residual amorphous matrix. The nanoscale α-Fe grains essentially depend on the competition between nucleation and grain growth. Nanocrystalline alloys are prepared by first preparing an amorphous alloy, and then precipitating nanocrystalline grains through isothermal annealing and other methods. Promoting nucleation and controlling grain growth during crystallization annealing are the key to preparing nanocrystalline alloys. Therefore, Cu elements that promote nucleation and Nb, Zr, Mo and other elements that inhibit grain growth are usually added to Fe-based nanocrystalline alloys. Although the iron-based nanocrystals (Fe-B-Si-Nb-Cu, the corresponding domestic grade is 1K107b) developed 30 years ago have shown excellent comprehensive soft magnetic properties that no other soft magnetic material has ever had, J s (saturation magnetic polarization intensity) is not high enough (J s 1.24T). Pursuing higher J s It is the main target of Fe-based nanocrystalline alloy research.

[0004] For nanocrystalline alloys, as the Fe content increases, J s As the research progressed, it was found that iron-based nanocrystalline alloys containing only Fe, Cu and metalloid elements (B, C, Si, P) could make J s Breakthrough 1.8T. However, alloying elements have a great influence on the forming ability and soft magnetic properties of nanocrystalline alloys, and there are interactions between alloying elements. Adding a certain type of metal element can improve one of the properties, but it will deteriorate other properties, which makes the effect of adding alloying elements more complicated. Therefore, in most iron-based soft magnetic nanocrystalline alloys, usually only 2 to 3 metalloid elements are contained, and nanocrystalline alloys containing four metalloid elements of B, C, Si, and P are rare.

[0005] In extreme cases, for higher Fe contents, metalloid elements with low atomic mass should be the most ideal. Fe-B nanocrystalline alloys can indeed obtain high Js and low H c However, the number of components is the key to determining the amorphous forming ability. When the Fe content is high, (1) the amorphous forming ability of the binary Fe-B system is very poor, and the raw material purity and process requirements are high; (2) the amorphous precursor has a higher first crystallization temperature, resulting in a lower difference between the first crystallization temperature and the second crystallization temperature, which deteriorates the process performance during crystallization annealing. Adding C to iron-based nanocrystals can improve the amorphous forming ability, but it will reduce the thermal stability of the system, increase the grain size, and deteriorate the soft magnetic properties of nanocrystalline alloys. The addition of Si can expand the crystallization process window of nanocrystalline alloys and improve the process performance of nanocrystalline alloys, but it will reduce J s . P will reduce the second crystallization temperature of the nanocrystalline precursor and reduce the temperature difference between the second crystallization temperature and the first crystallization temperature, thereby reducing the crystallization process window and thermal stability of the nanocrystalline alloy. Fe, B, C, Si and P have different degrees of positive and negative effects on the amorphous forming ability and soft magnetic properties, which makes it difficult to adjust a single alloying element to obtain a nano-alloy with excellent comprehensive performance during the design of nanocrystalline alloy composition.

[0006] Chinese patent CN111636039A discloses a Fe-BPC-Cu-M series amorphous nanocrystalline soft magnetic alloy with high saturation magnetization and its preparation method. s and low H c Chinese patent CN106756643A discloses an iron-based amorphous nanocrystalline soft magnetic alloy and a preparation method thereof, wherein the C content in the method is 0-1 at.%, and the low C content reduces the stability of the system, resulting in H c The existing technology can improve the performance of iron-based nanocrystalline soft magnetic alloys to a certain extent by regulating the alloy composition, but due to the complex interactions between the alloying elements of nanocrystalline alloys, it is difficult to develop the composition of iron-based nanocrystalline alloys, and it is still impossible to achieve high J at the same time. s and low H c . Summary of the invention

[0007] Therefore, the technical problem to be solved by the present invention is to overcome the defects in the prior art that iron-based nanocrystalline alloys are difficult to have both high saturation magnetic polarization intensity and low coercive force, have poor amorphous forming ability, and their soft magnetic properties need to be further improved, as well as the small difference between the first crystallization temperature and the second crystallization temperature of the amorphous precursor resulting in poor annealing process performance and being unsuitable for industrial production, thereby providing an iron-based nanocrystalline alloy with high saturation magnetic polarization intensity and a preparation method thereof.

[0008] To this end, the present invention provides the following technical solutions.

[0009] The present invention provides an iron-based nanocrystalline alloy with high saturation magnetic polarization strength, having a general formula as shown in Formula I,

[0010] Fe a B b C c Si d P e Cu f M g Formula I;

[0011] Wherein, a, b, c, d, e, f and g represent the atomic percentages of Fe, B, C, Si, P, Cu and M, respectively;

[0012] 81%≤a≤85%, 7%≤b≤12%; 0.0%≤g≤0.6%;

[0013] f / e≥0.8;

[0014] wherein the atomic percentage of carbon is not less than the atomic percentage of silicon and the atomic percentage of carbon is not less than the percentage of phosphorus; or, the sum of the atomic percentages of carbon and phosphorus is not less than the atomic percentage of silicon;

[0015] M is at least one of V, In, Bi and Sn.

[0016] In the high saturation magnetic polarization strength iron-based nanocrystalline alloy, the value ranges of c, d, e, f and g are respectively: 2.5%≤c≤4%, 1%≤d≤3%, 0.5%≤e≤1.5%, 0.5%≤f≤1.5%; and a+b+c+d+e+f+g=100%;

[0017] Preferably, 8%≤b≤12%, 2.8%≤c≤4%, 1%≤d≤3%, 0.8%≤e≤1.2%, and 0.75%≤f≤1.5%.

[0018] In the high saturation magnetic polarization intensity iron-based nanocrystalline alloy, the value ranges of b, c, d, e, f and g are 9%≤b≤12%, 2.8%≤c≤3%, 1%≤d≤3%, 0.8%≤e≤1.0%, and 0.75%≤f≤1.0%, respectively.

[0019] The high saturation magnetic polarization strength iron-based nanocrystalline alloy has the following structural formula:

[0020] Fe 83 B9C3Si3P1Cu1、Fe 83 B 8.75 C3Si3P1Cu 1.25 , Fe 83 B 11 C3Si1P1Cu1、Fe 85B8C4Si1P1Cu1、Fe 82.2 B 11.4 C 2.8 Si 1.8 P 0.8 Cu1, Fe 82.2 B 11.6 C 2.8 Si 1.8 P 0.8 Cu 0.8 , Fe 82.2 B 12 C 2.8 Si 1.2 P 0.8 Cu1, Fe 82.6 B 11 C 2.8 Si 1.8 P 0.8 Cu1, Fe 83.1 B 9.25 C3Si3P 0.9 Cu 0.75 , Fe 83 B 9.25 C3Si3P 0.9 Cu 0.75 Bi 0.1 , Fe 82.9 B 9.25 C3Si3P 0.9 Cu 0.75 Bi 0.1 In 0.1 , Fe 82.9 B 9.25 C3Si3P 0.9 Cu 0.75 Sn 0.1 Bi 0.1 or Fe 83.1 B 9.25 C3Si3P 0.9 Cu 0.75 .

[0021] Furthermore, the present invention also provides a method for preparing an iron-based nanocrystalline alloy with high saturation magnetic polarization intensity, comprising:

[0022] (1) Ingredients;

[0023] (2) smelting to obtain a master alloy;

[0024] (3) Amorphous alloy strips are produced by single-roll spinning method;

[0025] (4) Performing nanocrystallization heat treatment on the amorphous alloy strip.

[0026] Furthermore, after obtaining the master alloy, a step of purifying the master alloy is also included.

[0027] The purification includes placing the master alloy in a purification medium to repeatedly melt and solidify the master alloy several times until no bubbles are generated in the melt;

[0028] Preferably, the purification medium is boron oxide.

[0029] The melting temperature is at least 50K higher than the melting point of the master alloy.

[0030] The difference between the melting temperature and the melting point of the master alloy is 50-250K.

[0031] The temperature of the nanocrystallization heat treatment is higher than the temperature at which α-Fe begins to precipitate and lower than the temperature at which the Fe-type metal compound begins to precipitate.

[0032] The technical solution of the present invention has the following advantages:

[0033] 1. The high saturation magnetic polarization strength iron-based nanocrystalline alloy provided by the present invention has the general formula Fe a B b C c Si d P e Cu f M g , wherein a, b, c, d, e, f and g represent the atomic percentages of Fe, B, C, Si, P, Cu and M respectively; 81%≤a≤85%, 7%≤b≤12%; 0.0%≤g≤0.6%; f / e≥0.8; wherein the atomic percentage of carbon is not less than the atomic percentage of silicon and the atomic percentage of carbon is not less than the atomic percentage of phosphorus; or, the sum of the atomic percentages of carbon and phosphorus is not less than the atomic percentage of silicon; M is at least one of V, In, Bi and Sn. The high saturation magnetic polarization strength iron-based nanocrystalline alloy has high iron content, high saturation magnetic polarization strength, low coercive force, and does not contain other metal elements (such as precious metals), easily oxidizable elements and high melting point elements except for necessary copper and trace amounts of vanadium, indium, bismuth and tin. The raw material cost is low, the requirements for industrial production equipment are low, and it is conducive to industrial production.

[0034] The present invention is based on the study of the interaction and synergistic effect of each element, and makes full use of the interaction and synergistic effect between each alloying element to optimize the comprehensive performance of the iron-based nanocrystalline alloy. On the basis of ensuring high iron and boron content, the amount relationship between carbon, phosphorus and silicon and the copper-phosphorus ratio are strictly controlled to develop an iron-based nanocrystalline alloy with excellent soft magnetic properties. The iron-based nanocrystalline alloy has an ultra-high J of not less than 1.8T. s, the lowest coercive force can be 0.9A / m. The present invention can also ensure that the difference between the first crystallization temperature and the second crystallization temperature of the amorphous alloy strip (nanocrystalline precursor) is greater than 100K by controlling the atomic percentage of each component of the high saturation magnetic polarization strength iron-based nanocrystalline alloy and the relationship between each element. Since the temperature control is not precise during industrial production, if the first crystallization temperature and the second crystallization temperature are close, the process performance of the alloy will be reduced. The high saturation magnetic polarization strength iron-based nanocrystalline alloy of the present invention uses a specific ratio of raw materials to make the difference between the first crystallization temperature and the second crystallization temperature of the amorphous alloy strip large, which is suitable for industrial production, and the performance of the alloy will not be reduced during the crystallization process.

[0035] The high saturation magnetic polarization strength iron-based nanocrystalline alloy of the present invention uses a variety of metal elements (B, C, Si, P), and the alloy system is more complex in composition design, and the complex alloy system improves the amorphous forming ability. In addition, there are interactions and synergistic effects between the various alloying elements: the appropriate addition of boron can improve the amorphous forming ability of the system, but the addition of excessive boron will increase the first crystallization temperature of the system, thereby making the first crystallization temperature and the second crystallization temperature of the system close, which will reduce the process performance of the alloy and is not conducive to industrial production.

[0036] Carbon addition to J s The increase in J is due to two factors: the increase in alloy density and the weakening of the bonding between the metalloid-sp and metal-d orbitals. The addition of carbon weakens the bonding between the metalloid-sp and metal-d orbitals, resulting in a larger magnetic moment in the system, which has an impact on J s However, the addition of excessive carbon will reduce the intensity of magnetic exchange, thus making J s Although the metalloid element silicon is relatively unfavorable for obtaining a high magnetic moment, it can enhance the magnetic exchange interaction and increase the Curie temperature, which is beneficial to the Fe-based amorphous alloy J with high Fe content. s In addition, silicon has a high solid solubility in α-Fe. Appropriate silicon can regulate the saturation magnetostriction coefficient of α-Fe, reduce the overall saturation magnetostriction of the material, and thus reduce the coercive force. The appropriate ratio of carbon and silicon enables the system to have a higher magnetic moment, a stronger magnetic exchange interaction and a higher Curie temperature, thereby increasing the J of the material. sThe addition of phosphorus can improve the amorphous forming ability of the system, but it has a negative effect on the magnetic moment and is volatile. A small amount of copper addition will promote the formation of α-Fe, but excessive addition of copper will cause the amorphous forming ability of the material to decrease significantly. Therefore, the present invention utilizes the synergistic effect between the various alloying elements, fully optimizes the boron content, and the ratio of carbon and silicon elements, and limits the P and Cu content, while ensuring the amorphous forming ability (preparing completely amorphous strips is a prerequisite for preparing strips with stable and consistent performance. The better the amorphous forming ability, the easier it is to prepare completely amorphous strips, and the more stable the performance of the strips) while improving the saturation magnetic polarization intensity of the alloy system and reducing the coercive force.

[0037] 2. The high saturation magnetic polarization strength iron-based nanocrystalline alloy provided by the present invention is designed by designing the ratio of Fe, B, C, Si, P, Cu, M (V, In, Bi, Sn), so that the nanocrystalline alloy has both high saturation magnetic polarization strength and low coercive force. In addition, the iron-based nanocrystalline alloy has good amorphous forming ability and soft magnetic properties.

[0038] 3. The present invention provides a method for preparing an iron-based nanocrystalline alloy with high saturation magnetic polarization intensity. The iron-based nanocrystalline alloy with high saturation magnetic polarization intensity prepared by the method has both high saturation magnetic polarization intensity and low coercive force.

[0039] The atomic percentage of the high saturation magnetic polarization intensity iron-based nanocrystalline alloy component of the present invention can make the first crystallization temperature and the second crystallization temperature of the amorphous alloy strip have a large difference. During the nanocrystallization heat treatment process, it is beneficial to precipitate the α-Fe phase that improves the soft magnetic properties, and other phases that deteriorate the soft magnetic properties will not precipitate, thereby ensuring the amorphous forming ability and the soft magnetic properties of the nanocrystalline alloy. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0041] Figure 1 It is the corresponding XRD spectrum of the amorphous alloy strip before nanocrystallization heat treatment of Examples 1-8 of the present invention.

[0042] Figure 2 It is the corresponding XRD spectrum of the amorphous alloy strip before nanocrystallization heat treatment of Examples 9-12 of the present invention.

[0043] Figure 3 is Fe of Example 1 of the present invention 83Magnetic hysteresis loop of B9C3Si3P1Cu1 nanocrystalline alloy. DETAILED DESCRIPTION

[0044] The following examples are provided for a better understanding of the present invention, but are not intended to limit the best mode of implementation, nor to limit the content and protection scope of the present invention. Any product identical or similar to the present invention obtained by anyone under the inspiration of the present invention or by combining the features of the present invention with other prior arts shall fall within the protection scope of the present invention.

[0045] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.

[0046] The present invention provides an iron-based nanocrystalline alloy with high saturation magnetic polarization strength, having the general formula Fe a B b C c Si d P e Cu f M g , where a, b, c, d, e, f and g represent the atomic percentages of Fe, B, C, Si, P and Cu, respectively;

[0047] 81%≤a≤85%, 7%≤b≤12%; 0.0%≤g≤0.6%;

[0048] f / e≥0.8;

[0049] wherein the atomic percentage of carbon is not less than the atomic percentage of silicon and the atomic percentage of carbon is not less than the percentage of phosphorus; or, the sum of the atomic percentages of carbon and phosphorus is not less than the atomic percentage of silicon;

[0050] M is at least one of In, V, Bi and Sn.

[0051] Preferably, the value ranges of c, d, e, f and g are: 2.5%≤c≤4%, 1%≤d≤3%, 0.5%≤e≤1.5%, 0.5%≤f≤1.5%; and a+b+c+d+e+f+g=100%;

[0052] Preferably, 8%≤b≤12%, 2.8%≤c≤4%, 1%≤d≤3%, 0.8%≤e≤1.2%, 0.75%≤f≤1.5%, and 0.0%≤g≤0.6%.

[0053] The value of a can be any value between 81-85%, such as 84.5%, 84%, 83.5%, 83%, 82%, 82.5, 81%, etc.; the value of b can be any value between 7-12%, such as 8%, 8.5%, 9%, 9.5%, 10%, 10.5%, 11%, etc.; the value of c can be any value between 2.5-4%, such as 2.8%, 3.0%, 3.5%, 3.6%, etc. .2%, 3.6%, 3.9%, etc.; the value of d can be any value between 1-3%, such as 1.4%, 1.6%, 1.9%, 2.2%, 2.7%, 2.9%, etc.; the value of e can be any value between 0.8-1.2%, such as 0.9%, 1.0%, 1.1%, etc.; the value of f can be any value between 0.5-1.5%, such as 0.8%, 1.3%, etc.

[0054] The present invention provides a method for preparing an iron-based nanocrystalline alloy with high saturation magnetic polarization strength, the specific steps comprising:

[0055] (1) Ingredients: The ingredients are prepared according to the general formula of iron-based nanocrystalline alloys.

[0056] (2) Melting to obtain a master alloy; using an induction melting furnace or an arc melting furnace for melting, first evacuating the furnace, filling it with a protective gas, and then repeatedly melting the raw materials for 3-5 times to ensure that the components are evenly mixed, and then cooling to obtain a master alloy. Specifically, the protective gas can be an inert gas; more specifically, the protective gas can be argon.

[0057] Preferably, the method may further include a step of purifying the master alloy, specifically comprising placing the purification medium under vacuum conditions (less than 5 Pa), heating to 1200-1400 K to remove moisture, placing the master alloy in the purification medium when the purification medium becomes clear and free of bubbles and moisture, and raising the temperature by at least 50 K above the melting point of the master alloy to melt the master alloy, and then lowering the temperature to solidify the master alloy melt, repeating the melting-solidification step until no obvious bubbles are generated at the alloy interface when the master alloy is melted again, and completing the purification step. The purification step may be adjusted as required.

[0058] (3) The amorphous alloy strip is produced by a single-roll spinning method; the master alloy or the purified master alloy is placed in a single-roll spinning device to melt, and the master alloy melt is quickly cooled by the single-roll spinning method to obtain an amorphous alloy strip. Furthermore, the amorphous alloy strip is completely amorphous.

[0059] Preferably, the first crystallization temperature T of the amorphous alloy strip is x1 (corresponding to the temperature at which α-Fe begins to precipitate) and the second crystallization temperature T x2The difference (△T) between the temperature at which Fe-metal compounds begin to precipitate is greater than 100K, and the △T of amorphous alloy strips made with certain specific ratios can be as high as 160K.

[0060] (4) performing nanocrystallization heat treatment on the amorphous alloy strip; placing the amorphous alloy strip in a heat treatment device for nanocrystallization heat treatment to obtain a nanocrystalline alloy strip having body-centered cubic Fe nanoparticles uniformly precipitated in the amorphous matrix. The temperature of the nanocrystallization heat treatment is higher than the first crystallization temperature of the amorphous alloy strip and lower than the second crystallization temperature, so that the α-Fe phase can be precipitated, thereby improving the saturation magnetic polarization strength of the material, while avoiding the precipitation of the metal-like compound phase that degrades the coercivity, thereby ensuring the soft magnetic properties of the material.

[0061] Example 1

[0062] This embodiment provides an iron-based nanocrystalline alloy with high saturation magnetic polarization strength, the general formula is Fe 83 B9C3Si3P1Cu1;

[0063] The method for preparing the above-mentioned high saturation magnetic polarization strength iron-based nanocrystalline alloy comprises:

[0064] (1) Preparing ingredients according to the composition of the iron-based nanocrystalline alloy;

[0065] (2) Use an induction melting furnace for melting; first, the furnace cavity is evacuated and filled with a protective gas (argon), and then the raw materials are repeatedly melted 5 times to ensure uniform composition, and the corresponding master alloy is obtained after cooling.

[0066] (3) The prepared master alloy is placed in a single-roll quenching device for melting, and the master alloy melt is rapidly cooled by a single-roll quenching method (injection pressure 30 kPa, quenching line speed 40 m / s) to obtain an amorphous alloy strip.

[0067] (4) placing the amorphous alloy strip into a heat treatment device for nanocrystallization heat treatment at a temperature between the first crystallization temperature T x1 (corresponding to the temperature at which α-Fe begins to precipitate) and the second crystallization temperature T x2 (corresponding to the temperature at which Fe-type metal compounds begin to precipitate), specifically, the temperature of the nanocrystallization heat treatment is 723K, and a nanocrystalline alloy strip with a bandwidth of 65 mm is obtained, that is, a high saturation magnetic polarization strength iron-based nanocrystalline alloy. The saturation magnetic polarization strength (J s ), magnetic field strength under 800A / m (B 800 ), coercivity (H c ) and T x1 、T x2 and △T(△T=T x2 -Tx1 )See Table 1.

[0068] Example 2

[0069] This embodiment provides an iron-based nanocrystalline alloy with high saturation magnetic polarization strength, the general formula is Fe 83 B 8.75 C3Si3P1Cu 1.25 ;

[0070] The method for preparing the above-mentioned high saturation magnetic polarization strength iron-based nanocrystalline alloy comprises:

[0071] (1) Preparing ingredients according to the composition of the iron-based nanocrystalline alloy;

[0072] (2) Use an induction melting furnace for melting; first, the furnace cavity is evacuated and filled with a protective gas (argon), and then the raw materials are repeatedly melted 5 times to ensure uniform composition, and the corresponding master alloy is obtained after cooling.

[0073] (3) The prepared master alloy is placed in a single-roll quenching device for melting, and the master alloy melt is rapidly cooled by a single-roll quenching method (injection pressure 30 kPa, quenching line speed 40 m / s) to obtain an amorphous alloy strip.

[0074] (4) placing the amorphous alloy strip into a heat treatment device for nanocrystallization heat treatment at a temperature between the first crystallization temperature T x1 (corresponding to the temperature at which α-Fe begins to precipitate) and the second crystallization temperature T x2 (corresponding to the temperature at which Fe-type metal compounds begin to precipitate), specifically, the temperature of the nanocrystallization heat treatment is 713K, and a nanocrystalline alloy strip with a bandwidth of 1 mm is obtained, namely, an iron-based nanocrystalline alloy. The saturation magnetic polarization intensity (J s ), magnetic flux density under 800A / m (B 800 ), coercivity (H c ) and T x1 , T x2 and △T(△T=T x2 -T x1 )See Table 1.

[0075] Example 3

[0076] This embodiment provides an iron-based nanocrystalline alloy with high saturation magnetic polarization strength, the general formula is Fe 83 B 11 C3Si1P1Cu1;

[0077] The method for preparing the above-mentioned high saturation magnetic polarization strength iron-based nanocrystalline alloy comprises:

[0078] (1) Preparing ingredients according to the composition of the iron-based nanocrystalline alloy;

[0079] (2) Use an induction melting furnace for melting; first, the furnace cavity is evacuated and filled with a protective gas (argon), and then the raw materials are repeatedly melted 5 times to ensure uniform composition, and the corresponding master alloy is obtained after cooling.

[0080] (3) The prepared master alloy is placed in a single-roll quenching device for melting, and the master alloy melt is rapidly cooled by a single-roll quenching method (injection pressure 30 kPa, quenching line speed 40 m / s) to obtain an amorphous alloy strip.

[0081] (4) placing the amorphous alloy strip into a heat treatment device for nanocrystallization heat treatment at a temperature between the first crystallization temperature T x1 (corresponding to the temperature at which α-Fe begins to precipitate) and the second crystallization temperature T x2 (corresponding to the temperature at which Fe-type metal compounds begin to precipitate), specifically, the temperature of the nanocrystallization heat treatment is 723K, and a nanocrystalline alloy strip with a bandwidth of 1 mm is obtained, namely, an iron-based nanocrystalline alloy. The saturation magnetic polarization intensity (J s ), magnetic field strength under 800A / m (B 800 ), coercivity (H c ) and T x1 、T x2 and △T(△T=T x2 -T x1 )See Table 1.

[0082] Example 4

[0083] This embodiment provides an iron-based nanocrystalline alloy with high saturation magnetic polarization strength, the general formula is Fe 85 B8C4Si1P1Cu1;

[0084] The method for preparing the above-mentioned high saturation magnetic polarization strength iron-based nanocrystalline alloy comprises:

[0085] (1) Preparing ingredients according to the composition of the iron-based nanocrystalline alloy;

[0086] (2) Use an induction melting furnace for melting; first, the furnace cavity is evacuated and filled with a protective gas (argon), and then the raw materials are repeatedly melted 5 times to ensure uniform composition, and the corresponding master alloy is obtained after cooling.

[0087] (3) The prepared master alloy is placed in a single-roll quenching device for melting, and the master alloy melt is rapidly cooled by a single-roll quenching method (injection pressure 30 kPa, quenching line speed 40 m / s) to obtain an amorphous alloy strip.

[0088] (4) placing the amorphous alloy strip into a heat treatment device for nanocrystallization heat treatment at a temperature between the first crystallization temperature T x1 (corresponding to the temperature at which α-Fe begins to precipitate) and the second crystallization temperature T x2 (corresponding to the temperature at which Fe-type metal compounds begin to precipitate), specifically, the temperature of the nanocrystallization heat treatment is 723K, and a nanocrystalline alloy strip with a bandwidth of 1 mm is obtained, namely, an iron-based nanocrystalline alloy. The saturation magnetic polarization intensity (J s ), magnetic field strength under 800A / m (B 800 ), coercivity (H c ) and T x1 、T x2 and △T(△T=T x2 -T x1 )See Table 1.

[0089] Example 5

[0090] This embodiment provides an iron-based nanocrystalline alloy with high saturation magnetic polarization strength, the general formula is Fe 82.2 B 11.4 C 2.8 Si 1.8 P 0.8 Cu1;

[0091] The method for preparing the above-mentioned high saturation magnetic polarization strength iron-based nanocrystalline alloy comprises:

[0092] (1) Preparing ingredients according to the composition of the iron-based nanocrystalline alloy;

[0093] (2) Use an induction melting furnace for melting; first, the furnace cavity is evacuated and filled with a protective gas (argon), and then the raw materials are repeatedly melted 5 times to ensure uniform composition, and the corresponding master alloy is obtained after cooling.

[0094] (3) The prepared master alloy is placed in a single-roll quenching device for melting, and the master alloy melt is rapidly cooled by a single-roll quenching method (injection pressure 30 kPa, quenching line speed 35 m / s) to obtain an amorphous alloy strip.

[0095] (4) placing the amorphous alloy strip into a heat treatment device for nanocrystallization heat treatment at a temperature between the first crystallization temperature T x1 (corresponding to the temperature at which α-Fe begins to precipitate) and the second crystallization temperature T x2 (corresponding to the temperature at which Fe-type metal compounds begin to precipitate), specifically, the temperature of the nanocrystallization heat treatment is 783K, and a nanocrystalline alloy strip with a bandwidth of 1 mm is obtained, namely, an iron-based nanocrystalline alloy. The saturation magnetic polarization intensity (J s), magnetic flux density under 800A / m (B 800 ), coercivity (H c ) and T x1 , T x2 and △T(△T=T x2 -T x1 )See Table 1.

[0096] Example 6

[0097] This embodiment provides an iron-based nanocrystalline alloy with high saturation magnetic polarization strength, the general formula is Fe 82.2 B 11.6 C 2.8 Si 1.8 P 0.8 Cu 0.8 ;

[0098] The method for preparing the above-mentioned high saturation magnetic polarization strength iron-based nanocrystalline alloy comprises:

[0099] (1) Preparing ingredients according to the composition of the iron-based nanocrystalline alloy;

[0100] (2) Use an induction melting furnace for melting; first, the furnace cavity is evacuated and filled with protective gas (argon), and then the raw materials are repeatedly melted 5 times to ensure uniform composition, and the corresponding master alloy is obtained after cooling. When the master alloy is melted again, no obvious bubbles are generated at the alloy interface, and the purified master alloy is obtained after cooling.

[0101] (3) The prepared master alloy is placed in a single-roll quenching device for melting, and the master alloy melt is rapidly cooled by a single-roll quenching method (injection pressure 30 kPa, quenching line speed 30 m / s) to obtain an amorphous alloy strip.

[0102] (4) placing the amorphous alloy strip into a heat treatment device for nanocrystallization heat treatment at a temperature between the first crystallization temperature T x1 (corresponding to the temperature at which α-Fe begins to precipitate) and the second crystallization temperature T x2 (corresponding to the temperature at which Fe-type metal compounds begin to precipitate), specifically, the temperature of the nanocrystallization heat treatment is 743K, and a nanocrystalline alloy strip with a bandwidth of 1 mm is obtained, namely, an iron-based nanocrystalline alloy. The saturation magnetic polarization intensity (J s ), magnetic flux density under 800A / m (B 800 ), coercivity (H c ) and T x1 , T x2 and △T(△T=T x2 -T x1 )See Table 1.

[0103] Example 7

[0104] This embodiment provides an iron-based nanocrystalline alloy with high saturation magnetic polarization strength, the general formula is Fe 82.2 B 12 C 2.8 Si 1.2 P 0.8 Cu1;

[0105] The method for preparing the above-mentioned high saturation magnetic polarization strength iron-based nanocrystalline alloy comprises:

[0106] (1) Preparing ingredients according to the composition of the iron-based nanocrystalline alloy;

[0107] (2) Use an induction melting furnace for melting; first, the furnace cavity is evacuated and filled with a protective gas (argon), and then the raw materials are repeatedly melted 5 times to ensure uniform composition, and the corresponding master alloy is obtained after cooling.

[0108] (3) The master alloy is placed in a single-roll quenching device for melting, and the master alloy melt is rapidly cooled by a single-roll quenching method (injection pressure 30 kPa, quenching line speed 40 m / s) to obtain an amorphous alloy strip.

[0109] (4) placing the amorphous alloy strip into a heat treatment device for nanocrystallization heat treatment at a temperature between the first crystallization temperature T x1 (corresponding to the temperature at which α-Fe begins to precipitate) and the second crystallization temperature T x2 (corresponding to the temperature at which Fe-type metal compounds begin to precipitate), specifically, the temperature of the nanocrystallization heat treatment is 743K, and a nanocrystalline alloy strip with a bandwidth of 1 mm is obtained, namely, an iron-based nanocrystalline alloy. The saturation magnetic polarization intensity (J s ), magnetic flux density under 800A / m (B 800 ), coercivity (H c ) and T x1 , T x2 and △T(△T=T x2 -T x1 )See Table 1.

[0110] Example 8

[0111] This embodiment provides an iron-based nanocrystalline alloy with high saturation magnetic polarization strength, the general formula is Fe 82.6 B 11 C 2.8 Si 1.8 P 0.8 Cu1;

[0112] The method for preparing the above-mentioned high saturation magnetic polarization strength iron-based nanocrystalline alloy comprises:

[0113] (1) Preparing ingredients according to the composition of the iron-based nanocrystalline alloy;

[0114] (2) Use an induction melting furnace for melting; first, the furnace cavity is evacuated and filled with a protective gas (argon), and then the raw materials are repeatedly melted 5 times to ensure uniform composition, and the corresponding master alloy is obtained after cooling.

[0115] (3) The prepared master alloy is placed in a single-roll quenching device for melting, and the master alloy melt is rapidly cooled by a single-roll quenching method (injection pressure 30 kPa, quenching line speed 40 m / s) to obtain an amorphous alloy strip.

[0116] (4) placing the amorphous alloy strip into a heat treatment device for nanocrystallization heat treatment at a temperature between the first crystallization temperature T x1 (corresponding to the temperature at which α-Fe begins to precipitate) and the second crystallization temperature T x2 (corresponding to the temperature at which Fe-type metal compounds begin to precipitate), specifically, the temperature of the nanocrystallization heat treatment is 763K, and a nanocrystalline alloy strip with a bandwidth of 1 mm is obtained, namely, an iron-based nanocrystalline alloy. The saturation magnetic polarization intensity (J s ), magnetic flux density under 800A / m (B 800 ), coercivity (H c ) and T x1 , T x2 and △T(△T=T x2 -T x1 )See Table 1.

[0117] Example 9

[0118] This embodiment provides an iron-based nanocrystalline alloy with high saturation magnetic polarization strength, the general formula is Fe 83.1 B 9.25 C3Si3P 0.9 Cu 0.75 ;

[0119] The method for preparing the above-mentioned high saturation magnetic polarization strength iron-based nanocrystalline alloy comprises:

[0120] (1) Preparing ingredients according to the composition of the iron-based nanocrystalline alloy;

[0121] (2) Use an induction melting furnace for melting; first, the furnace cavity is evacuated and filled with a protective gas (argon), and then the raw materials are repeatedly melted 5 times to ensure uniform composition, and the corresponding master alloy is obtained after cooling.

[0122] (3) The prepared master alloy is placed in a single-roll quenching device for melting, and the master alloy melt is rapidly cooled by a single-roll quenching method (injection pressure 30 kPa, quenching line speed 40 m / s) to obtain an amorphous alloy strip.

[0123] (4) placing the amorphous alloy strip into a heat treatment device for nanocrystallization heat treatment at a temperature between the first crystallization temperature T x1 (corresponding to the temperature at which α-Fe begins to precipitate) and the second crystallization temperature T x2 (corresponding to the temperature at which Fe-type metal compounds begin to precipitate), specifically, the temperature of the nanocrystallization heat treatment is 763K, and a nanocrystalline alloy strip with a bandwidth of 1 mm is obtained, namely, an iron-based nanocrystalline alloy. The saturation magnetic polarization intensity (J s ), magnetic field strength under 800A / m (B 800 ), coercivity (H c ) and T x1 、T x2 and △T(△T=T x2 -T x1 )See Table 1.

[0124] Example 10

[0125] This embodiment provides an iron-based nanocrystalline alloy with high saturation magnetic polarization strength, the general formula is Fe 83 B 9.25 C3Si3P 0.9 Cu 0.75 Bi 0.1 ;

[0126] The method for preparing the above-mentioned high saturation magnetic polarization strength iron-based nanocrystalline alloy comprises:

[0127] (1) Preparing ingredients according to the composition of the iron-based nanocrystalline alloy;

[0128] (2) Use an induction melting furnace for melting; first, the furnace cavity is evacuated and filled with a protective gas (argon), and then the raw materials are repeatedly melted 5 times to ensure uniform composition, and the corresponding master alloy is obtained after cooling.

[0129] (3) The prepared master alloy is placed in a single-roll quenching device for melting, and the master alloy melt is rapidly cooled by a single-roll quenching method (injection pressure 30 kPa, quenching line speed 40 m / s) to obtain an amorphous alloy strip.

[0130] (4) placing the amorphous alloy strip into a heat treatment device for nanocrystallization heat treatment at a temperature between the first crystallization temperature T x1 (corresponding to the temperature at which α-Fe begins to precipitate) and the second crystallization temperature T x2(corresponding to the temperature at which Fe-type metal compounds begin to precipitate), specifically, the temperature of the nanocrystallization heat treatment is 763K, and a nanocrystalline alloy strip with a bandwidth of 1 mm is obtained, namely, an iron-based nanocrystalline alloy. The saturation magnetic polarization intensity (J s ), magnetic flux density under 800A / m (B 800 ), coercivity (H c ) and T x1 , T x2 and △T(△T=T x2 -T x1 )See Table 1.

[0131] Embodiment 11

[0132] This embodiment provides an iron-based nanocrystalline alloy with high saturation magnetic polarization strength, the general formula is Fe 82.9 B 9.25 C3Si3P 0.9 Cu 0.75 Bi 0.1 In 0.1 ;

[0133] The method for preparing the above-mentioned high saturation magnetic polarization strength iron-based nanocrystalline alloy comprises:

[0134] (1) According to the composition of the iron-based nanocrystalline alloy, industrial raw materials are used for batching;

[0135] (2) Use an induction melting furnace for melting; first, the furnace cavity is evacuated and filled with a protective gas (argon), and then the raw materials are repeatedly melted 5 times to ensure uniform composition, and the corresponding master alloy is obtained after cooling.

[0136] (3) The master alloy is placed in a single-roll quenching device for melting, and the master alloy melt is rapidly cooled by a single-roll quenching method (injection pressure 30 kPa, quenching line speed 40 m / s) to obtain an amorphous alloy strip.

[0137] (4) placing the amorphous alloy strip into a heat treatment device for nanocrystallization heat treatment at a temperature between the first crystallization temperature T x1 (corresponding to the temperature at which α-Fe begins to precipitate) and the second crystallization temperature T x2 (corresponding to the temperature at which Fe-type metal compounds begin to precipitate), specifically, the temperature of the nanocrystallization heat treatment is 763K, and a nanocrystalline alloy strip with a bandwidth of 1 mm is obtained, namely, an iron-based nanocrystalline alloy. The saturation magnetic polarization intensity (J s ), magnetic flux density under 800A / m (B 800 ), coercivity (H c ) and T x1 , Tx2 and △T(△T=T x2 -T x1 )See Table 1.

[0138] Example 12

[0139] This embodiment provides an iron-based nanocrystalline alloy with high saturation magnetic polarization strength, the general formula is Fe 82.9 B 9.25 C3Si3P 0.9 Cu 0.75 Sn 0.1 Bi 0.1 ;

[0140] The method for preparing the above-mentioned high saturation magnetic polarization strength iron-based nanocrystalline alloy comprises:

[0141] (1) According to the composition of the iron-based nanocrystalline alloy, industrial raw materials are used for batching;

[0142] (2) Use an induction melting furnace for melting; first, the furnace cavity is evacuated and filled with a protective gas (argon), and then the raw materials are repeatedly melted 5 times to ensure uniform composition, and the corresponding master alloy is obtained after cooling.

[0143] (3) The master alloy is placed in a single-roll quenching device for melting, and the master alloy melt is rapidly cooled by a single-roll quenching method (injection pressure 30 kPa, quenching line speed 40 m / s) to obtain an amorphous alloy strip.

[0144] (4) placing the amorphous alloy strip into a heat treatment device for nanocrystallization heat treatment at a temperature between the first crystallization temperature T x1 (corresponding to the temperature at which α-Fe begins to precipitate) and the second crystallization temperature T x2 (corresponding to the temperature at which Fe-type metal compounds begin to precipitate), specifically, the temperature of the nanocrystallization heat treatment is 763K, and a nanocrystalline alloy strip with a bandwidth of 1 mm is obtained, namely, an iron-based nanocrystalline alloy. The saturation magnetic polarization intensity (J s ), magnetic flux density under 800A / m (B 800 ), coercivity (H c ) and T x1 , T x2 and △T(△T=T x2 -T x1 )See Table 1.

[0145] Example 13

[0146] This embodiment provides an iron-based nanocrystalline alloy with high saturation magnetic polarization strength, the general formula is Fe 83.1 B 9.25 C3Si3P0.9 Cu 0.75 ;

[0147] The method for preparing the above-mentioned high saturation magnetic polarization strength iron-based nanocrystalline alloy comprises:

[0148] (1) Preparing ingredients according to the composition of the iron-based nanocrystalline alloy;

[0149] (2) Use an induction melting furnace for melting; first, the furnace cavity is evacuated and filled with a protective gas (argon), and then the raw materials are repeatedly melted 5 times to ensure uniform composition, and the corresponding master alloy is obtained after cooling.

[0150] The master alloy is purified. The purification medium is boron oxide. The purification medium is placed under a vacuum condition of less than 5Pa and heated to 1200K to remove moisture. When the boron oxide becomes clear and free of bubbles and moisture, the master alloy is placed in the boron oxide medium and heated to 1400K to melt the master alloy. The master alloy is then cooled to completely solidify. The master alloy is then heated again to melt again. The melting and cooling are repeated until no obvious bubbles are generated at the alloy interface when the master alloy is melted again. The master alloy is then cooled to obtain the purified master alloy.

[0151] (3) The prepared master alloy is placed in a single-roll quenching device for melting, and the master alloy melt is rapidly cooled by a single-roll quenching method (injection pressure 30 kPa, quenching line speed 40 m / s) to obtain an amorphous alloy strip.

[0152] (4) placing the amorphous alloy strip into a heat treatment device for nanocrystallization heat treatment at a temperature between the first crystallization temperature T x1 (corresponding to the temperature at which α-Fe begins to precipitate) and the second crystallization temperature T x2 (corresponding to the temperature at which Fe-type metal compounds begin to precipitate), specifically, the temperature of the nanocrystallization heat treatment is 763K, and a nanocrystalline alloy strip with a bandwidth of 2 mm is obtained, namely, an iron-based nanocrystalline alloy. The saturation magnetic polarization intensity (J s ), magnetic field strength under 800A / m (B 800 ), coercivity (H c ) and T x1 、T x2 and △T(△T=T x2 -T x1 )See Table 1.

[0153] Comparative Example 1

[0154] This comparative example provides an iron-based nanocrystalline alloy with the general formula of Fe 83.3 B8Si4P4Cu 0.7 (NANOMET) nanocrystalline alloy strip, the preparation method is the same as that of Example 1.

[0155] Comparative Example 2

[0156] This comparative example provides an iron-based alloy, which is Fe-3wt%Si (non-oriented).

[0157] Comparative Example 3

[0158] This comparative example provides an iron-based alloy, which is Fe-6.5wt%Si (non-oriented).

[0159] Test example

[0160] This test example provides the performance test and test results of the iron-based nanocrystalline alloy provided in each embodiment and comparative example, as follows:

[0161] (1) Testing method for the saturation magnetic polarization intensity of Fe-based nanocrystalline alloys: The saturation magnetic polarization intensity (J) of the sample was measured using a vibrating sample magnetometer (VSM). s ) to test and get J s .

[0162] The BH hysteresis loop was used to measure the B 800 and H c (The maximum external magnetic field is 800A / m) for testing. The results are shown in Table 1. Figure 3 This is the hysteresis loop of the nanocrystalline alloy strip of Example 1.

[0163] (2) X-ray diffraction (XRD) was used to test the amorphous alloy strips prepared in each embodiment to determine the physical phase of the strips. When preparing the iron-based nanocrystalline alloy in each embodiment, the XRD results of the amorphous alloy strips are shown in FIG. Figure 1 and Figure 2 .

[0164] (3) Using differential scanning calorimetry (DSC) to perform thermal analysis on the amorphous alloy strips prepared in each embodiment, the first crystallization temperature T of the amorphous alloy strips was obtained. x1 (corresponding to the temperature at which α-Fe begins to precipitate) and the second crystallization temperature T x2 (corresponding to the temperature at which Fe-type metal compounds begin to precipitate). The crystallization heat treatment temperature of each embodiment is determined by the first crystallization temperature. During the crystallization heat treatment process, the crystallization temperature is selected to ensure that Fe-type metal compounds do not precipitate. x1 and T x2 See Table 1.

[0165] Table 1 Performance test results of iron-based nanocrystalline alloys prepared in various embodiments and comparative examples

[0166]

[0167] It can be seen from the above results that the nanocrystalline alloy strip prepared by the present invention has high saturation magnetic polarization intensity and low coercive force, and the difference between the two crystallization temperatures of the amorphous alloy strip is large, which is conducive to industrial production.

[0168] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from these are still within the scope of protection of the invention.

Claims

1. An iron-based nanocrystalline alloy with high saturation magnetic polarization strength, characterized in that: Having the general formula shown in Formula I, Fe a B b C c Si d P e Cu f M g Formula Ⅰ; Wherein, a, b, c, d, e, f and g represent the atomic percentages of Fe, B, C, Si, P, Cu and M, respectively; 81%≤a≤85%, 7%≤b≤12%; 0.0%≤g≤0.6%; f / e≥0.8; wherein the atomic percentage of carbon is not less than the atomic percentage of silicon and the atomic percentage of carbon is not less than the percentage of phosphorus; or, the sum of the atomic percentages of carbon and phosphorus is not less than the atomic percentage of silicon; M is at least one of V, In, Bi and Sn.

2. The high saturation magnetic polarization strength iron-based nanocrystalline alloy according to claim 1, characterized in that: The value ranges of c, d, e, f and g are: 2.5%≤c≤4%, 1%≤d≤3%, 0.5%≤e≤1.5%, 0.5%≤f≤1.5%; and a+b+c+d+e+f+g=100%; Preferably, 8%≤b≤12%, 2.8%≤c≤4%, 1%≤d≤3%, 0.8%≤e≤1.2%, and 0.75%≤f≤1.5%.

3. The high saturation magnetic polarization strength iron-based nanocrystalline alloy according to claim 1 or 2, characterized in that: The value ranges of b, c, d, e, f and g are 9%≤b≤12%, 2.8%≤c≤3%, 1%≤d≤3%, 0.8%≤e≤1.0% and 0.75%≤f≤1.0% respectively.

4. The high saturation magnetic polarization strength iron-based nanocrystalline alloy according to any one of claims 1 to 3, characterized in that: It has the following structural formula: Fe 83 B9C3Si3P1Cu1, Fe 83 B 8.75 C3Si3P1Cu 1.25 , Fe 83 B 11 C3Si1P1Cu1, Fe 85 B8C4Si1P1Cu1, Fe 82.2 B 11.4 C 2.8 Si 1.8 P 0.8 Cu1, Fe 82.2 B 11.6 C 2.8 Si 1.8 P 0.8 Cu 0.8 , Fe 82.2 B 12 C 2.8 Si 1.2 P 0.8 Cu1, Fe 82.6 B 11 C 2.8 Si 1.8 P 0.8 Cu1, Fe 83.1 B 9.25 C3Si3P 0.9 Cu 0.75 , Fe 83 B 9.25 C3Si3P 0.9 Cu 0.75 Bi 0.1 , Fe 82.9 B 9.25 C3Si3P 0.9 Cu 0.75 Bi 0.1 In 0.1 , Fe 82.9 B 9.25 C3Si3P 0.9 Cu 0.75 Sn 0.1 Bi 0.1 or Fe 83.1 B 9.25 C3Si3P 0.9 Cu 0.75 .

5. The method for preparing the iron-based nanocrystalline alloy with high saturation magnetic polarization intensity according to any one of claims 1 to 4, characterized in that: include, (1) Ingredients; (2) smelting to obtain a master alloy; (3) Amorphous alloy strips are produced by single-roll spinning method; (4) Performing nanocrystallization heat treatment on the amorphous alloy strip.

6. The preparation method according to claim 5, characterized in that: After obtaining the master alloy, the method further includes the step of purifying the master alloy.

7. The preparation method according to claim 6, characterized in that: The purification includes placing the master alloy in a purification medium to repeatedly melt and solidify the master alloy several times until no bubbles are generated in the melt; Preferably, the purification medium is boron oxide.

8. The preparation method according to claim 7, characterized in that: The melting temperature is at least 50K higher than the melting point of the master alloy.

9. The preparation method according to claim 8, characterized in that: The difference between the melting temperature and the melting point of the master alloy is 50-250K.

10. The preparation method according to any one of claims 5 to 9, characterized in that: The temperature of the nanocrystallization heat treatment is higher than the temperature at which α-Fe begins to precipitate and lower than the temperature at which the Fe-type metal compound begins to precipitate.

Citation Information

Patent Citations

  • Iron-based amorphous and nano-crystalline soft magnetic alloy and preparation method thereof

    CN106756643A

  • High-saturation-magnetization-intensity Fe-B-P-C-Cu-M series amorphous nanocrystal soft magnetic alloy and preparation method

    CN111636039A